Dekomodifikasi Ruang Domestik: Resistensi Ibu terhadap Kapitalisme Perhatian Digital - Rofian Dedi Susanto; Achmad Jamil; Alfirahmi (LUGAS Jurnal Komunikasi, 2026)
The expansion of digital media has transformed domestic spaces into arenas for the commodification of children's leisure time, disrupting family communication structures. Departing from the dominant literature that views shifts in parental authority solely through a relational lens, this qualitative single-case study examines digital parenting practices through the critical paradigm of the Political Economy of Media and the Culture Industry. Located in the peri-urban area of Depok, this study analyzes the tactics of a full-time stay-at-home mother in mitigating algorithmic hegemony over her three children (aged 11, 8, and 5). Data were gathered through naturalistic non-participant observation and in-depth interviews. The findings reveal that children's consistent preference for YouTube content (such as reaction videos and gameplay) is not a manifestation of free choice but rather an expression of pseudo-individuality constructed by the platform's addictive design. The mother responds to this exploitation of attention capitalism through moral curation by offering educational alternatives; however, these efforts are frequently thwarted. As an ultimate resolution, the mother reclaims the children's cognitive space by enforcing absolute biological routines (nap and bath times) and accompanying them with vocal escalation. This physical and repressive approach proves to be the most effective instrument for de-commodification to sever the digital screen's annexation. This article enriches the discourse of critical communication studies by positioning household routines as micro-resistance instruments against technological commercialization.